Amino acid mutagenesis within ligand-binding loops in αv confers loss-of-function or gain-of-function phenotype on integrin αvβ3 - Honda, Shigenori; Kashiwagi, Hirokazu; Kiyoi, Teruo; Kato, Hisashi; Kosugi, Satoru; Shiraga, Masamichi; Kurata, Yoshiyuki; Tomiyama, Yoshiaki (Thrombosis and Haemostasis, 2004)
The crystal structure of αvβ3 in complex with a cyclic RGDcontaining ligand has recently been demonstrated. However, the functional significance of each residue within ligand binding loops has not been fully elucidated. Here, by employing alaninescanning mutagenesis, we have examined the functional role of ligand contact residues in αv. Tyr178 –> Ala substitution (Tyr178Ala) and Asp218Ala abolished a monovalent ligand, WOW-1 Fab binding as well as soluble fibrinogen binding, which is in perfect agreement with the crystallography. However, Asp150Ala showed no or only a modest inhibition of ligand binding. In contrast, Tyr substitution at Ala215 (Ala215Tyr) increased WOW-1 Fab binding, suggesting that the substitution increased the integrin affinity. The adhesion assay to immobilized fibrinogen showed essentially the same data as obtained using soluble ligands. Our present data indicate that Tyr178 and Asp218, but not Asp150 in αv is critically involved in ligand-binding and that Ala215 could regulate the affinity of αvβ3.
Keywords: β-propeller; cation-π interaction; gain-of-function; ligand-binding site; loss-of-function